The Disquiet of Quiet Quitting: Definitional Clarity, Theoretical Pathways, and Future Research - Magrizos, Solon; Aydinliyim, Lauren E.; Roumpi, Dorothea; Porter, Caitlin M.; Phillips, Jean M.; Delery, John E. (Human Resource Management, 2026)
ABSTRACT Quiet quitting (QQ) has emerged as a prominent topic in both popular press and academic research, reflecting shifts in employees' engagement, effort allocation, and responses to contemporary work pressures. This review synthesizes findings from 11 papers published in a recent Special Issue on The Disquiet of Quiet Quitting . We integrate conceptual, empirical, and methodological insights from these papers and other recent literature to clarify what QQ is and what it is not. We highlight the multidimensional nature of QQ, distinguishing deliberate and passive forms, reactive versus value‐driven motivations, and variations in scope and behavioral expression. We then propose a 2 × 2 typology of quiet quitters (Protesters, Faders, Boundary Setters, and Indifferent Drifters) constructed along two key dimensions, intentionality and motivational basis, to capture the heterogeneity of behaviors and underlying motives. Finally, we discuss implications for theory, measurement, and practice, emphasizing how QQ signals broader dynamics in employment relationships, including fairness, well‐being, and sustainable engagement, and we identify directions for future research, including longitudinal, multi‐level, and cross‐cultural investigations.